Assessing the acceptance of augmented‐reality and head‐mounted display in medicine counselling. (21st March 2022) - Prenzler, Shane; Anoopkumar‐Dukie, Shailendra; Grant, Gary
Abstract: Background: Both head‐mounted display (HMD) and augmented reality (AR) are examples of emergent and disruptive technologies that have had little exposure in pharmacy. The developed HMD‐AR warfarin counselling guide allowed pharmacists to examine this technology in a familiar context. Aims: To determine acceptance among pharmacists for the HMD‐AR warfarin counselling guide, as a form of emergent and disruptive technology. Methods: Forty Australian community pharmacists were recruited for a cohort study. The study was completed in a pre‐ and post‐test manner, where pharmacists were allowed to explore the HMD‐AR warfarin counselling guide. The pre‐test included questions related to demographic variables. The post‐test used Technology Assessment Model (TAM) based Likert scale questions on a 1–5 (strongly agree to strongly disagree) scale. Questions unrelated to TAM were also included in the pre‐ and post‐test and compared using a Wilcoxon signed‐rank test. These engaged participants on perceived usefulness of the HMD‐AR warfarin counselling guide and their willingness to use technology. Qualitative feedback to open ended questions in the post‐test was also sought. Results: Technology Assessment Model constructs (perceived ease‐of‐use, perceived usefulness, and behavioural intention) indicated a positive reception overall. Pre‐ and post‐test questions regarding perceived usefulness of the HMD‐AR warfarin counselling guide and willingness to use technology declined after using the HMD‐AR warfarin counselling guide. Conclusion: Participant expectations although still positive, declined after using the HMD‐AR warfarin counselling guide. Further study is needed for technological advances, design optimisation and to assess patient acceptance to ensure the system is fit for purpose for pharmacy practice.